How the great scientists reasoned : the scientific method in action - Tibbetts, Gary G. (Elsevier insights., 2013)
The scientific method is one of the most basic and essential concepts across the sciences, ensuring that investigations are carried out with precision and thoroughness. The scientific method is often taught as a step-by-step approach, but real examples from history are not always given. This book teaches the basic modes of scientific thought, not by philosophical generalizations, but by illustrating in detail how great scientists from across the sciences solved problems using scientific reason. Examples include Christopher Columbus, Joseph Priestly, Antoine Lavoisier, Michael Faraday, Wilhelm Rontgen, Max Planck, Albert Einstein, and Niels Bohr. Written by a successful research physicist who has engaged in many studies and years of research, all in the attempt to extract the secrets of nature, this book captures the excitement and joy of research. The process of scientific discovery is as delightfully absorbing, as complex, and as profoundly human as falling in love. It can be a roller coaster ride of despairing valleys and exhilarating highs. This book sketches the powerful reasoning which led to many different discoveries, but also celebrates the "ah-ha moments" experienced by each scientist, letting readers share the thrilling instant when each scientist reached the critical revelation in his research. Places the scientific method in context using historical examplesSuitable for both scientists and non-scientists looking to better understand scientific reasoningWritten in an engaging style with clear illustrations and referencing.